Boosting students' speaking ability through Community Language Learning - Halimah Halimah (Universitas Syiah Kuala, 2018)
This study was done to find out the effect of using the Community Language Learning (CLL) Method for teaching-learning speaking English with second semester students in the English Education Study Program at a private university in West Java in an effort to improve the English speaking skills of the students. This study used an action research method where the researcher was accompanied by an observer as a collaborator. Three cycles were done for this study. Data were gathered from observations, a questionnaire, interviews and tests. In the preliminary study, the mean score of the student's speaking was 61. The percentage of students who passed the minimum criterion of 70 was 22% with only 6 out of 27 students passing the minimum score. The mean score from post-test 1 was 63 and only 7 students or 26% passed the minimum score. The mean score from post-test 2 was 76 and 89%, i.e. 24 students passed the minimum score. While from post-test 3 the mean score was 84 and all of the students (100%) passed the minimum score. Hence the results showed that the use of the CLL method was a success. The students enjoyed their lessons more, and were more motivated, interested and confident during the teaching-learning sessions.